1986
DOI: 10.1002/ijc.2910380303
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia serum reactive with retrovirus‐related antigen in normal human placenta

Abstract: Serum antibody reactive with a retrovirus-related p30 antigen in human normal term placenta was investigated and characterized by immunohistologic and immunoblotting methods. Sera obtained from patients with acute leukemia and malignant lymphoma were used as first antibody, and cryostat sections of placenta were the target antigen. An IgM antibody that reacted mainly with the basal aspect of syncytiotrophoblast of chorionic villi, where a putative human endogenous retrovirus p30 antigen is located, was directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Rabson et al (1985) detected transcripts of the env gene of clone 4-1 in normal human placenta. Maeda et al (1986) also reported that antiserum reactive with the human endogenous retrovirus p30 reacted with syncytiotrophoblasts. The reagent prepared for our study identified a molecule of 38 kDa in placental syncytiotrophoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Rabson et al (1985) detected transcripts of the env gene of clone 4-1 in normal human placenta. Maeda et al (1986) also reported that antiserum reactive with the human endogenous retrovirus p30 reacted with syncytiotrophoblasts. The reagent prepared for our study identified a molecule of 38 kDa in placental syncytiotrophoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…30,000 Da ''physiochemically similar to reference murine and primate type C retrovirus p30s and antigenically cross-reactive with p30 of the simian sarcoma-associated virus and gibbon ape leukemia virus primate retrovirus group.'' In a subsequent study, Maeda et al (114) reported that sera obtained from patients with acute leukemia and malignant lymphoma contained an immunoglobulin M antibody that reacted with placental syncytiotrophoblasts. It occurred less frequently in the sera of pregnant women and healthy controls.…”
Section: Expression Of Herv Antigens In Placental Tissuesmentioning
confidence: 97%
“…It occurred less frequently in the sera of pregnant women and healthy controls. The main reactive antigen was reported to be a nonglycosylated 32-Da protein that was antigenically related to simian sarcoma-associated virus p30 (114).…”
Section: Expression Of Herv Antigens In Placental Tissuesmentioning
confidence: 99%
“…It occurred less frequently in the sera of pregnant women and healthy controls. The main reactive antigen was reported to be a nonglycosylated 32-Da protein that was antigenically related to simian sarcoma-associated virus p30 (114). The studies of Kurth et al (97) revealed a very interesting pattern of antibodies to type C viral antigens in patients with testicular teratocarcinomas.…”
Section: Expression Of Herv Antigens In Placental Tissuesmentioning
confidence: 99%